Fearless minds : rights based approach to organizing and advocacy - Pandit, Vivek (Pune : National Centre for Advocacy Studies, 2000)
With reference to social marginality in India and advocacy for mitigating the malaise; a study.
Keywords: Marginality, Social -- India; Social advocacy -- India